Improving the work process efficiency of a tillage module for pre-sowing tillage - Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Tesliuk, Hennadiy; Теслюк, Геннадій Володимирович; Puhach, Andriy; Пугач, Андрій Миколайович; Kobets, Oleksandr; Кобець, Олександр Миколайович; Zolotovska, Olena; Золотовська, Олена Володимирівна; Boiko, Vladislav; Бойко, Владислав Борисович (PC Technology Center, 2023)
The formation of a differentiated structure of the arable horizon during the pre-sowing processing of the grant is a relevant task that can be solved by designing appropriate soil-processing technical means. A scientific hypothesis has been put forward, according to which increasing the efficiency of the process of forming a differentiated structure of the arable horizon can be achieved by improving the design and substantiating the structural and technological parameters of the tillage module for pre-sowing tillage. Numerical simulation was carried out in the Simcenter STAR-CCM+ software package using the Lagrangian multiphase model employing the discrete element method. Calculation of second-order regression equations and statistical processing of the obtained data was carried out in the Wolfram Cloud software package. As a result of the simulation of the improved design of the tillage module, which includes one drum, plowshare, casing, and cleaner, it was found that it performs the operation of separation and redistribution of soil aggregates with almost the same efficiency as the basic design with 2 drums and plowshare. As a result of the simulation of the work process of the improved tillage module, regression equations of the content of the 10–30 mm fraction in the 0–4 cm soil layer and the content of the 0–10 mm fraction in the 4–8 cm soil layer from the research factors were obtained. The chosen factors of influence were a casing outlet clearance, casing inlet clearance angle, cleaner inclination angle, drum rotation frequency, unit movement speed, and processing depth. Solving the problem of multi-criteria optimization, the rational structural and technological parameters of the tillage module for pre-sowing tillage were calculated. Формування диференційованої структури орного горизонту під час передпосівної обробки гранту є актуальним завданням, яке може бути вирішене шляхом проектування відповідних ґрунтообробних технічних засобів. Висунуто наукову гіпотезу, згідно з якою підвищення ефективності процесу формування диференційованої структури орного горизонту можна досягти шляхом удосконалення конструкції та обґрунтування конструктивно-технологічних параметрів ґрунтообробного модуля передпосівного обробітку ґрунту. Чисельне моделювання проводили в програмному комплексі Simcenter STAR-CCM+ з використанням багатофазної моделі Лагранжа методом дискретних елементів. Розрахунок рівнянь регресії другого порядку та статистичну обробку отриманих даних проводили в пакеті програм Wolfram Cloud. У результаті моделювання удосконаленої конструкції ґрунтообробного модуля, який включає один барабан, леміш, кожух і очисник, встановлено, що він виконує операцію сепарації та перерозподілу ґрунтових агрегатів практично з тією ж ефективністю, що й базовий конструкція з 2 барабанами і лемешем. У результаті моделювання процесу роботи удосконаленого модуля обробітку ґрунту отримані рівняння регресії вмісту фракції 10–30 мм у шарі 0–4 см ґрунту та вмісту фракції 0–10 мм у 4– З досліджуваних факторів отримано шар ґрунту 8 см. Обраними факторами впливу були вихідний зазор обсадної труби, кут входу обсадної труби, кут нахилу очисника, частота обертання барабана, швидкість руху агрегату та глибина обробки. Вирішуючи задачу багатокритеріальної оптимізації, розраховано раціональні конструктивно-технологічні параметри ґрунтообробного модуля для передпосівного обробітку ґрунту.
Підвищення ефективності роботи ґрунтообробного модуля для передпосівного обробітку ґрунту
Keywords: soil environment; ґрунтове середовище; arable horizon; орний горизонт; differentiated structure; диференційована структура; presowing treatment; передпосівна обробка; моделювання; modelling